The use of gamified differentiated homework in teaching General Chemistry 1 - Villamor, Edelito G. (Animo Repository, 2021)
Blended learning, where the lack of interaction between teacher and students and the “one-size-fits-all” self-learning modules that do not cater to various learners’ learning capabilities, make teaching and learning General Chemistry during this time of pandemic more difficult. Students are becoming less self-regulated because the teacher is not physically present to monitor their work and the lack of differentiation in activities makes learners lose their motivation. This action research aimed to integrate gamification and differentiation in students’ homework to make learning General Chemistry fun and engaging. Classcraft was used as an online gamification platform to improve students’ motivation, and the homework tasks were differentiated to suit their varying level of learning readiness. This Gamified Differentiated Homework in teaching four modules in General Chemistry 1 to Grade 11 – STEM students were studied using validated questionnaires called Student Perception in Homework Questionnaire and Chemistry Motivation Questionnaire (CMQ) II. The students’ Experience Points were used to measure their academic performance. To elucidate the context behind the quantitative results, a focus group discussion was conducted. The results revealed that students were very engaged in doing their homework because of the gamification and differentiation elements. Their motivation in learning chemistry remained high and did not show a significant increase or decrease after the four-week intervention. The students’ accumulated Experience Points revealed that they performed best only at the start of the quarter then slightly dropped and plateaued in the following weeks due to increasing difficulty of the lessons and voluminous tasks given by other teachers.